4.4 kV β-Ga2O3 MESFETs with power figure of merit exceeding 100 MW cm−2. (1st June 2022) - Bhattacharyya, Arkka; Sharma, Shivam; Alema, Fikadu; Ranga, Praneeth; Roy, Saurav; Peterson, Carl; Seryogin, Geroge; Osinsky, Andrei; Singisetti, Uttam; Krishnamoorthy, Sriram
Abstract: β -Ga2 O3 metal–semiconductor field-effect transistors are realized with superior reverse breakdown voltages ( V BR ) and ON currents ( I DMAX ). A sandwiched SiN x dielectric field plate design is utilized that prevents etching-related damage in the active region and a deep mesa-etching was used to reduce reverse leakage. The device with L GD = 34.5 μ m exhibits an I DMAX of 56 mA mm −1, a high I ON / I OFF ratio >10 8 and a very low reverse leakage until catastrophic breakdown at ∼4.4 kV. A power figure of merit (PFOM) of 132 MW cm −2 was calculated for a V BR of ∼4.4 kV. The reported results are the first >4 kV class Ga2 O3 transistors to surpass the theoretical unipolar FOM of silicon.